(untitled) (International Journal of Food and Nutritional Sciences, 2022)
It has been aimed to examine the effect of pinealectomy or enucleation followed by exogenous melatonin treatment on air-breathing activity rhythm in Indian freshwater catfish, Clarias batrachus. Following 7 days of acclimation, animals (n=16) were randomly selected from the stock aquaria and were kept in specially designed glass aquaria inside the chronocubicles exposed under L: D 12:12 (lights on at 0600 hrs). Light schedule was maintained with the help of automatic timers. All the animals remain intact (IG) for first 7 days and then divided into two groups. In the first group (n=08) bilateral ocular enucleation was performed and were left for next 21 days. In the second group (n=08) pinealectomy was performed and were left for next 10 days. Then the individuals of both the groups received daily late afternoon treatment (17:00-18:00hrs) of melatonin (2g/fish) for next 10 days. The air–breathing activity was recorded with the help of infrared photoswitches connected to a microprocessor based event recorder. The results obtained by actograms revealed that maximum no. of individuals remained entrained to the LD cycle in both intact and pinealectomized group. After melatonin treatment in the same group, the actograms depicted that air-breathing activity in five individuals was entrained atleast with the lights off time and, the greatest part of their activity was noticed during light phase of the LD regime. Further, a statistically significant 24-h rhythm in air-breathing activity was also detected in intact, pinealectomization and melatonin treatment. In the other group, all the enucleated Clarias batrachus were desynchronized to the LD cycle. The acrophases of the activity were located during the photophase of the LD regime in 5 out of 8 individuals. Further, 3 out of eight enucleated melatonin receiving Clarias batrachus apparently entrained to lights off time. In addition, 5 (Fish # 09,10, 11, 13, 15) out of 8 Clarias batrachus retained a statistically significant 24-h rhythm in their air-breathing activity and period () of activity was prominent 24-h in Fish # 09, 11, 13, 14.